Moroccan Strawberry Tree (Arbutus unedo L.) Fruits: Nutritional Value and Mineral Composition - Zakaria Ait lhaj; Rahma Bchitou; Fatima Gaboun; Rabha Abdelwahd; Tarik Benabdelouahab; Mohammed Rachid Kabbour; Paul Pare; Ghizlane Diria; Khadija Bakhy (Foods, 2021)
The strawberry tree (Arbutus unedo L.), grown throughout the Mediterranean, produces edible fruit; as it is easily bruised, the sweet, reddish fruit is used mostly to prepare jams, marmalades and alcoholic beverages. As the genus is paraphyletic, phytochemical analysis can assist in defining the fruit composition with the species Arbutus unedo L. (A. unedo). Here we report on the carbohydrate, total sugar, protein, fat, fiber, ash, and mineral content of wild fruit, harvested from 45 specimens from five locations. The dominant nutrients were carbohydrates (78.2–84.8 g/100 g), total sugars (52.1–67.2 g/100 g) and dietary fiber (11.0–20.1 g/100 g). Other important nutrients supplied by A. unedo fruit include P, K, and Fe. The fruit was observed to contain health-promoting components providing 42 and 36%, of recommended daily allowance (RDA) for fiber and zinc, respectively, as well as iron and manganese, at levels exceeding minimum RDA. The free-sugar profile revealed high glucose followed by fructose content with minor amounts of sucrose (14, 11, and 6 g/100 g, respectively). Significant differences both between regions and within individuals were observed for several traits. The richness of fruit nutrients in A. unedo confers nutritional value and as such, a promising alternative fruit source.